KEY COMPETENCE AS A BASIS FOR INNOVATION PROJECTS MANAGEMENT - Lyudmyla Chernova (Сучасний стан наукових досліджень та технологій в промисловості)
By the implementing an enterprise development program, the existing key competence of the organization may undergo significant changes.  Also introducing innovations, you can get not only benefits, but additional problems and even risks.  It should be noted that an organization may have more than one key competence, especially when we deal with changes in the management structure or entering new markets.  For this class of tasks, the classical linear optimization problem does not fit, since it does not take into account the additional conditions that arise when an organization transitions from one state to another, precisely due to the implementation of the development program.  Therefore, to solve this problem, we need a dual problem. The subject of research in this article is the process of introducing key competence, as the main component of the management of innovative projects in the organization.  Objective: to develop a tool for introducing key competence into an organization’s work by solving a dual linear optimization problem. Tasks: to analyze the factors influencing the results and the possibility of introducing key competence in the organization’s activities, to obtain a general algorithm for the transition from direct to dual competence. Research methods: logical generalization, analysis and synthesis, structural analysis. Results: The article considers the key competence of the enterprise as the main component of the management of innovative projects, which the company implements.  Shown her place and the role that she plays.  A project description model has been developed, which describes processes that take into account the impact of the production and economic system on project implementation. The article proposes a general algorithm for constructing pairs of dual linear optimization problems.  The existing schemes of transition from a direct problem to a dual one are meaningful.  Considering this fact, a generalized algorithm for generating pairs of related problems has been proposed and strictly proved. Formalization of the developed scheme makes it easy to get the correct pairs of dual problems.  It is shown that the analysis of the key competence of the enterprise makes it possible to offer a new base for the formation of a strategic plan, the implementation of which will lead to the emergence (support) of a sustainable competitive advantage, as well as assess its potential in terms of financial plan and capabilities of the enterprise or business system as a whole. Conclusions: The tools for analysis and implementation of key competence in the organization’s activities have been developed. The results obtained in during the study allow us to state that a new base has been proposed for the formation of a strategic plan for the development of an enterprise, the use of this base will lead to a sustainable competitive advantage, which will become possible when implementing key competences in the process of changing the management structure.  Taking into account that an organization can have more than one key competence, the second competence is dual to the original, that allows a general transition from direct to dual competence.